2020
DOI: 10.3390/su122310099
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphological Map and Quaternary Landscape Evolution of the Monfragüe Park (Cáceres, Spain)

Abstract: From the geomorphological cartography, the geometric and spatial distribution of the quaternary forms and deposits are analyzed, with special relevance to the fluvial terraces that allow obtaining the chronology of the successive landscape changes of the course of the Tagus River attributed to the activity of the Fault of Alentejo-Plasencia (APF). The “Appalachian” relief of Monfragüe National Park, constituting a series of quartzitic combs with direction NW, between which they find slopes, hills and valleys f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…The divergence of the two other lineages comprising the western and the eastern Alagón sub‐basin populations (V1 and V2) also occurred during the Pleistocene (Chibanian period, ~80,000 Mya). The complex geology of the Alagón sub‐basin is evident by the anomalous current trajectory of some of its rivers (Carrasco & Pedraza, 1991 ; Díez Herrero, 2003 ; Goy et al, 2020 ; Jiménez, 1994 ; Schnabel & Gutiérrez, 2014 ). For instance, the two banks of the Alagón sub‐basin, represented by the two mitochondrial lineages, are currently joined by the mouth of the Árrago River in the Alagón River, that is, the main river of the western and the eastern Alagón sub‐basin, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The divergence of the two other lineages comprising the western and the eastern Alagón sub‐basin populations (V1 and V2) also occurred during the Pleistocene (Chibanian period, ~80,000 Mya). The complex geology of the Alagón sub‐basin is evident by the anomalous current trajectory of some of its rivers (Carrasco & Pedraza, 1991 ; Díez Herrero, 2003 ; Goy et al, 2020 ; Jiménez, 1994 ; Schnabel & Gutiérrez, 2014 ). For instance, the two banks of the Alagón sub‐basin, represented by the two mitochondrial lineages, are currently joined by the mouth of the Árrago River in the Alagón River, that is, the main river of the western and the eastern Alagón sub‐basin, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported on the genetic structure of freshwater fauna associated with connections between the Tagus Basin and adjacent basins (e.g., Alagón, Alberche and Lozoya rivers; Carmona et al, 2000 ; Casas‐Sainz & De Vicente, 2009 ; Doadrio, 1988 ; Pérez‐González, 1980 ; Sousa‐Santos et al, 2007 ). Although recent connections may be explained as a consequence of the tectonic activity in the region (Goy et al, 2020 ), there are no geological studies that support a recent connection between the western Alagón sub‐basin (Tagus Basin) and the Águeda sub‐basin (Duero Basin), despite the close proximity of some of their river headwaters (in some cases, as little as 150 m of linear distance). A connection, however, has been hypothesized to explain the co‐occurrence of individuals with the mitochondrial genome of Squalius carolitertii (distributed in the Duero Basin) and those of S .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…El pie de loma, situado en la base de las lomas, es similar a geoformas receptoras de flujos de agua y materiales clasificadas como terraza inferior, lomerío bajo plano a ligeramente convexo y pie de colina (Solís-Castillo et al, 2014;Brindis-Santos et al, 2020;Goy et al, 2020) Schoeneberger et al, 2017;Vanacker et al, 2019;Goy et al, 2020). La cumbre sobresale en el lomerío por su posición topográfica elevada y extensión (18.5 %), concuerda con geoformas indicadoras de erosión e intemperización como terrazas cumbrales y cumbres (Solís-Castillo et al, 2014;Frugoni et al, 2016) Cabe hacer notar que las formas de pie de loma, hombro y pozo petrolero han sido omitidas en la cartografía geomorfológica de lomeríos, posiblemente por su escasa superficie, y generalmente se incluyen en las laderas.…”
Section: Geomorfológico De Lomeríounclassified